Clinical profile and outcome of snake bite in children admitted in a tertiary care institute in the metropolitan city of Karnataka, India - Chandrashekaraswamy, Shivaprakash Sosale; Verghese, Deepthy; Reddy, Chikkanarasa (International Journal of Contemporary Pediatrics, 2020)
Background: Snake bite is a major medical and public health problem in tropical agricultural world. A high incidence of snake bite envenomation has been reported from rural India, many times the incidence is underestimated due to lack of epidemiological information. The present study analyses the age, mode of presentation, seasonal variation, clinical profile, management and outcome of patients with snake bite in below 18 years of age group of a metropolitan city, India. Methods: This study is a retrospective single centre study conducted in government referral hospital in Bangalore from January 2016 to January 2020 including 53 patients, who presented with a history of snake bite. Clinical data about age, sex, clinical manifestations, complications, management and outcome were analysed. Results: In our study including of 53 patients, maximum snake bites incidents were noted in age group of 6-10 years (47.16%) of the rural population with male predominance (83.01%). Most of the bites occurred during monsoon season (54.71%) in evening time. Bite marks were observed mainly on lower limbs in 71.69% of patients. Tourniquet was the commonly used first aid care (67.92%). Most of the bites were vasculotoxic in (75.47%) followed by neuroparalytic in 15 patients (9.43%) and maximum cases responded to 20 vials of ante venom. Mortality was nil. Conclusions: Snake bite is a life-threatening emergency. The key in minimizing mortality and severe morbidity is aggressive management of sick patient and timely as well as judicious administration of ante snake venom. There is a requirement to sensitize the general public and healthcare personnel on preventive measures, emergency care and treatment of snake bites. The serious clinical features of snake bite warrant early referral and management in tertiary care centers.